On the Concept of Sustainable Recreational Use of Natural Resources of Cross- Border Areas of Altai - HARMS, Evgenia O.; SUKHOVA, Maria G.; KOCHEEVA, Nina A.; MINAEV, Alexander I.; KARANIN, Andrey V. (Journal of Environmental Management and Tourism, 2016)
The article describes the geo-ecological principles and their relationship with the sustainable development of natural resources. The authors propose conceptual illustration of sustainable recreational use of natural resources of cross-border areas of Altai and analyze the main diversification paths of the tourism product of the region. Cross-border cooperation between the countries of the region and the organization of a single eco-economic and recreational space is of special importance as it is the basis of sustainable mutually beneficial economic development. The authors carried out the systematization of the concepts of sustainable recreational use of natural resources and grounded its geo-ecological principles as exemplified by crossborder areas of Altai.
Keywords: Altai; recreational resources; tourism; sustainable development